Investigation of the natural mineral quartz treated underwater electric discharge - Shaimerdenova, G.M.; Bulkairova, G.A.; Sadenova, K.K.; Sagimbekova, M.N. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Аrticle is discusses the results of studies of the electrohydraulic method of destruction of natural mineral quartz. Examined some types of quartz and its use in production. The electroimpulse technology is one of acceptable methods of crushing and milling of natural minerals. Shows the results of laboratory tests obtained with different diameters fractions. Information obtained from the milling of metallurgical silicium with help of offered technology in the future can be applied in production.
Keywords: electrohydroimpulse installation; electrohydraulic effect; quartzite deposit of "Nadyrbay"; crushing